Effects of dietary gelatinized starch on growth performance, glucose metabolism, oxidative status and fillet texture of rice field eel (Monopterus albus). (7th July 2021) - Deng, Yao; Wu, Huadong; Zhou, Jiujie; Wu, Shanshan; Che, Changbao; Hu, Yi; Yan, Quangen; Zhou, Qiubai; Jiang, Wenhao; Huo, Huanhuan; He, Zhigang; Peng, Mo
Abstract: A 47‐day feeding trial was conducted to investigate the effects of increasing dietary carbohydrates on the growth performance, nutrient metabolism, oxidative status and fillet texture of rice field eel ( Monopterus albus ). Three isonitrogenous (39%) and isoenergetic diets (17.7 kJ/g) were formulated with 16% (S16), 28% (S28) or 40% (S40) gelatinized starch. Each diet was randomly fed to triplicate cages with 60 fish in each replicate cage. The results suggested that the growth of M . albus was independent of dietary treatments. Higher level of gelatinized starch (40%) displayed a negative impact on intestinal amylase and trypsin enzymes, concurrent with impaired liver function in terms of higher activities of serum alanine aminotransferase and alkaline phosphatase. Although the higher gelatinized starch could inhibit the activities of enzymes involved in glycolysis (pyruvate kinase and phosphofructokinase) and gluconeogenesis (fructose‐1, 6‐bisphosphatase), the hepatic glycogen content was observed to be positively associated with gelatinized starch level. High gelatinized starch had negative effects on intestinal antioxidant capacity by suppressing the activities of glutathione peroxidase and total superoxide dismutase. In addition, dietary starch could influence the fillet texture of M . albus by affecting hardness, springiness and chewiness. S40 group displayed a significant increase in the hardness of fillet, whilst the chewiness and springiness of fillet in S28 group were remarkably lower than those in the other groups. Overall, these results indicated that M . albus could tolerate 40% gelatinized starch level without significant impacts on growth performance, whilst excessive gelatinized starch might exert negative impacts on digestive enzyme activities and antioxidant capacity after 47 days of feeding.